Impact of Various Variables on Teachers Commitment Towards Secondary School - Gaurav Rustgi; Vandana Goswami; Varsha Rustagi (Integrated Journal for Research in Arts and Humanities, 2022)
Growth of education sector can be expanded, if the faculties; teaching in the education sector are satisfied and committed. They are the asset to the organization. They are the one who can bring and responsible for bringing the positive changes in the society. They act as a powerful tool for moulding the behaviour of the students. They instruct, guide and give direction to the students so that the students can have healthy growth and stable life. They provide the creativity, innovative ideas for growth of the students and provide necessary knowledge not only relevant to the subjects but also give knowledge for their social and economic development. The present Study has attempted to investigate the relationship between Teacher Commitment of secondary school and age, sex and marital status. The Study was carried out on a selected sample (614) secondary school teachers drawn from various secondary schools of Delhi NCR. The descriptive analysis, ‘t’ test, percentage, frequency was applied to realize the objectives. Data was collected and analyzed with the help of SPSS package. Based on the data analysis major findings and conclusion were drawn.